Sensitivity Analysis of Phase 5 Batu Hijau Pit Walls - Khatib Syarbini; Faesal, Andi; Za Munarfan Putra; Syamsul Hidayat; Hermansyah, Wahyu; Erintina, Melinda Dwi; Ubaidillah, Aji Syailendra; Dermawan, Iwan; Azhari, Uraihan; Hakim, Muhammad Samsul (UIR PRESS, 2025)
The Batu Hijau mine, an extensive copper-gold operation in West Sumbawa, Indonesia, employs an open-pit mining method and is characterized by its significant pit dimensions, with planned slope heights reaching up to 1000 meters. Given the scale of the operation, maintaining slope stability is critical, influenced by stress on the pit slopes, geological structures, mine geometry, and rock mass strength. This study investigates the impact of groundwater on slope stability, emphasizing the role of groundwater pressure in reducing shear strength and consequently affecting slope stability. A comprehensive sensitivity analysis was conducted to evaluate the influence of groundwater pressures on the stability of the Batu Hijau pit walls. This analysis utilized the SLIDE® software from Rocsience, incorporating Rock Mass Rating parameters derived from geotechnical drill hole logs and mapping data, which were integrated into a 3D block model using Minesight™. The analysis focused on two groundwater conditions: Water Surface and Pore Pressure Grid. Groundwater model conditions were based on piezometer data and a new groundwater conceptual model of the Batu Hijau pit walls. Results from sensitivity assessments shows that high pore pressure will decease the slope stability. This findings highlight the need to manage groundwater pressures within the pit walls to mitigate slope instability effectively,therefore, the safety of mining operational could be increased. This study provides valuable insights into groundwater pressure management and its implications for slope stability in large-scale open-pit mining operations.